Ethics in the workplace - Bredeson, Dean; Goree, Keith (Mason, Ohio : South-Western/Cengage Learning, 2012)
Combines foundation in classic and contemporary theory, examples and analysis drawn from the workplace, ethical decision-making models, and a constant focus on self-reflection and moral reasoning
1. Welcome to ethics -- 2. Ethical principles -- 3. Personal ethical development -- 4. Shareholder theory and stakeholder theory -- 5. Ethical selling, marketing, and advertising -- 6. Technology, testing, and workplace privacy -- 7. Ethics and discrimination -- 8. Ethics for employees -- 9. Ethical lending and the "great recession" -- 10. Two global issues: the environment and sweatshops -- 11. Critical thinking in ethics
Includes bibliographical references and index
Keywords: Business ethics